Low cost business model in passenger railway transportation - Toman, Ivo; Zelený, Lubomír; Sklenář, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
Investigation of potential implementation of low-cost business model in passenger railway transportation. Analysis of techniques used in different industries and evaluation of potential of such techniques.
Vedoucí práce: Lubomír Zelený
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses